(untitled) (Bioscience Journal, 2019)
In the State of Rio Grande do Sul (RS), Southern Brazil, glyphosate has not been capable of controlling wild poinsettia (Euphorbia heterophylla L.) in soybean fields, thus, suggesting resistance to this herbicide. Therefore, this study aimed at evaluating sensitivity of wild poinsettia biotypes to glyphosate, identifying the occurrence of resistance of wild poinsettia to the herbicide in RS state and determining the resistance factor of wild poinsettia biotypes under suspicion, besides assessing other herbicides as alternative controls. Two greenhouse experiments, which lasted two years, were conducted by a completely randomized design with four replications. Six biotypes (Factor A) and eight doses of glyphosate (Factor B) were used for getting the dose-response curve. Regarding the alternative control, post-emergence herbicides for soybean and corn crops were tested. Control and dry mass of the shoot were analyzed as variables. Resistance factors of resistant biotypes 20.2 and 21.1 were 4.83 and 5.29, respectively, by comparison with the susceptible biotype (11.4). In RS state, there has currently been high selection pressure due to the intensive use of glyphosate against wild poinsettia plants, as the result of the occurrence of biotypes 20.2 and 21.1 which have low levels of resistance to glyphosate and very little control by ALS-inhibiting herbicides. Therefore, an alternative to mitigate the problem is the use of herbicides with different mechanisms of action.